2018
DOI: 10.2147/mder.s166999
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a new reaction by-product in BDDE cross-linked autoclaved hyaluronic acid hydrogels by LC–MS analysis

Abstract: BackgroundHyaluronic acid (HA), a naturally occurring polysaccharide, is used in the production of dermal fillers for esthetic purposes. As it has a few days of half-life in human tissues, HA-based dermal filler is chemically modified to increase its lifetime in the body. The most common modification used in commercial HA-based filler is the cross-linking of HA chains using 1,4-butanediol diglycidyl ether (BDDE) as cross-linking agent. Residual, or unreacted, BDDE is considered nontoxic when it is <2 parts per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
0
28
0
1
Order By: Relevance
“…When using HA fillers for volume augmentation, we should take into consideration that most of this HA products, especially those that give more volume to the tissue, are made out of reticulated HA. This reticulation can be obtained with different reticulating agents and the toxicity of this molecules in the long term is not clearly understood in most cases 5 . Therefore, agarose can be a good alternative for those patients starting with filler or for those that have already received multiple injections with reticulated HA 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When using HA fillers for volume augmentation, we should take into consideration that most of this HA products, especially those that give more volume to the tissue, are made out of reticulated HA. This reticulation can be obtained with different reticulating agents and the toxicity of this molecules in the long term is not clearly understood in most cases 5 . Therefore, agarose can be a good alternative for those patients starting with filler or for those that have already received multiple injections with reticulated HA 12…”
Section: Discussionmentioning
confidence: 99%
“…One of the problems of reticulated HA fillers is that they include different types of reticulating agents in order to maintain the filler structure, such as 1,4‐butanediol diglycidyl ether (BDDE). Although HA is itself a natural and safe molecule, already present naturally in our normal skin, the reticulating agents can be toxic when deposited in higher concentrations 5 …”
Section: Introductionmentioning
confidence: 99%
“…Az oedema lehet lokalizált vagy generalizált, kifejezetten súlyos és elhúzódó. Kezelésében orális kortikoszteroid és antihisztamin jön szóba (28).…”
Section: Táblázatunclassified
“…The most popular type of filler contains hyaluronic acid (HA). However, the use of HA fillers carries an inherent risk of hypersensitivity reactions because these fillers contain hyaluronan-related proteins and 1,4-butanediol diglycidyl ether (BDDE) 5,6 . In addition, small fragments of HA can cause inflammation and elicit adverse effects that include erythema, slight oedema, hematoma, itching, and pain [7][8][9] .…”
mentioning
confidence: 99%
“…In addition, small fragments of HA can cause inflammation and elicit adverse effects that include erythema, slight oedema, hematoma, itching, and pain [7][8][9] . A recent study showed that the biocompatibility of HA-based materials decreases with an increase in the number of modifications to this polysaccharide 5,6,10 .…”
mentioning
confidence: 99%